Material windows and working stations. The discourse networks behind skeuomorphic interface in Pathfinder: Kingmaker - Żmuda, Michał Dawid (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The article probes the intermedial structure of the skeuomorphic interface in Pathfinder: Kingmaker. The author indicates that intermedia research in game studies is often diachronically limited, focusing on material and semiotic interactions between “old” and “new” media. He proposes to open the field onto historically aware discoursive analysis and bases his method on Friedrich Kittler’s notion of “discourse networks”. This allows him to inspect the game in relation to technologically-founded networks that embody or bring into life specific modes of though and experience. During his analysis, he discovers that the interface design is involved with navigation devices in Late Medieval and Early Renaissance periods, Alberti’s windows as objects through with narrative spaces become visible, isometric modes of objective thinking, industrial and cybernetic notions of control, and the Xerox invention of the computer as a working environment.